PENERAPAN STRATEGI KREATIF-PRODUKTIF UNTUK MENINGKATKAN HASIL BELAJAR FISIKA SISWA KELAS X MAN 1 PEKANBARU PADA ASPEK KETERAMPILAN PSIKOMOTOR DAN SOSIAL - Yennita Yennita; Nisfullail Nisfullail; Naila Husna (Jurnal Geliga Sains: Jurnal Pendidikan Fisika, 2009)
This study aims to determine the effectiveness of the application of learning strategies in acreative-productive aspects of learning physics in psychomotor skills and social skills of students.The subject matter is selected physical quantities and units. Research subjects were 34 students ingrade X3 MAN 1 Pekanbaru. Data collection instrument is a test of learning psychomotor skills andsocial skills of observation sheet. Psychomotor skills tests administered after learning is completedwhile the social skills of students is done by directly observing the social interactions of studentsduring the learning process. The research data were analyzed descriptively. The results of theanalysis of data on psychomotor skills learning outcomes of students showed that the averageabsorption was 88.5%, exhaustiveness student learning in the classical 85.3% while thecompleteness of material is 100 %. The results of the analysis of data on social skills showed thatan increase in the number of students who have social skills at each meeting. At the last meeting,otherwise categorized high social skills. Thus, the relevance of creative - productive learningstrategies to learning outcomes psychomotor skills and social skills expressed high so that it can beconcluded that the creative - productive learning strategy is expressed effectively applied toimprove psychomotor skills and social skills class X MAN 1 Pekanbaru.